Endothelin-1 stimulates the Na+/Ca2+ exchanger reverse mode through intracellular Na+ (Na+i)-dependent and Na+i-independent pathways - Aiello, Ernesto Alejandro (2005)
This study aimed to explore the signaling pathways involved in the positive inotropic effect (PIE) of low doses of endothelin-1 (ET-1). Cat papillary muscles were used for force and intracellular Na(+) concentration (Na(+)(i)) measurements, and isolated cat ventricular myocytes for patch-clamp experiments. ET-1 (5 nmol/L) induced a PIE and an associated increase in Na(+)(i) that were abolished by Na(+)/H(+) exchanger (NHE) inhibition with HOE642. Reverse-mode Na(+)/Ca(2+) exchanger (NCX) blockade with KB-R7943 reversed the ET-1-induced PIE. These results suggest that the ET-1-induced PIE is totally attributable to the NHE-mediated Na(+)(i) increase. However, an additional direct stimulating effect of ET-1 on NCX after the necessary increase in Na(+)(i) could occur. Thus, the ET-1-induced increase in Na(+)(i) and contractility was compared with that induced by partial inhibition of the Na(+)/K(+) ATPase by lowering extracellular K(+) (K(+)(o)). For a given Na(+)(i), ET-1 induced a greater PIE than low K(+)(o). In the presence of HOE642 and after increasing contractility and Na(+)(i) by low K(+)(o), ET-1 induced an additional PIE that was reversed by KB-R7943 or the protein kinase C (PKC) inhibitor chelerythrine. ET-1 increased the NCX current and negatively shifted the NCX reversal potential (E(NCX)). HOE642 attenuated the increase in NCX outward current and abolished the E(NCX) shift. These results indicate that whereas the NHE-mediated ET-1-induced increase in Na(+)(i) seems to be mandatory to drive NCX in reverse and enhance contractility, Na(+)(i)-independent and PKC-dependent NCX stimulation appears to additionally contribute to the PIE. However, it is important to stress that the latter can only occur after the primary participation of the former.